Competitive intelligence for business: A study on facebook as a marketing strategy / Balqis Fatanah Md Musadek - Balqis Fatanah , Md Musadek (2017)
During the early stage of business processes, the Competitive Intelligence (CI) (Sazrinee, et al., 2014) process of a particular competitor was acquired manually from trade journals and periodicals, which are both intensive resource and time consuming. However, in the current era, with the exponential growth of technologies, businesses can easily obtain consumers information via the World Wide Web. The current food and beverage companies in Malaysia are currently utilising the Internet as a source of information for Competitive Intelligence. However the use of Facebook is limited for promoting product and services. The objectives of this research are to investigate the adoption of Facebook usage on the Internet by food and beverage companies in Malaysia as a source of information for CI that is used for marketing strategy; as well as to investigate the utilisation of Facebook as a marketing strategy by five food and beverage companies in Malaysia as a source of information for CI. Methodologies that have been used for internet adoption are from Walczuch et.al. (2000) study and Facebook as International eMarketing Strategy of Taiwan Hotels (Hsu, 2012). A survey on the Internet adoption in Malaysian food and beverages services sector was conducted as part of the study and results show Internet adoption is significant to perceived benefits, ways of using the Internet, attitude towards the Internet and concern regarding Internet access. The results from the study on Internet adoption also show that the food and beverage companies in Malaysia has still limited usage of Facebook to promote product or services and used for marketing strategies. The results from the second objective shows that the Malaysian food and beverages companies have the capability to improve their business performance via the use of Social Network Sites (SNS) such as Facebook, in order to disseminate marketing campaigns and gain information on its competitors. Hence, businesses can directly gain leverage from Facebook as a platform for sourcing information related to the CI process, and therefore can successfully design an effective marketing strategy for food and beverage companies.